Registration of 'CP 09‐1952' Sugarcane. Issue 3 (9th August 2018) - Davidson, R. Wayne; Gordon, Vanessa S.; Sandhu, Hardev S.; McCord, Per; Zhao, Duli; Comstock, Jack C.; Singh, Maninder P.; Sood, Sushma; Baltazar, Miguel; McCorkle, Katherine
Abstract : 'CP 09‐1952' (Reg. No. CV‐179, PI 686942) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the USDA–ARS, the University of Florida, and the Florida Sugarcane League, Inc. At the 6 June 2016 Florida Sugarcane Variety Committee Meeting, CP 09‐1952 was released to growers for organic (muck) soils in Florida, and seed cane was made available in September 2016. CP 09‐1952 was selected from a polycross of CP 01‐2390 × Poly 06‐30 made at Canal Point, FL, in January 2007. The female parent, CP 01‐2390, is not a commercial cultivar. The male parent is unknown, as it is one of 15 clones comprising the polycross. Cane yield of CP 09‐1952 on muck soils, averaged across 19 harvests through three crop cycles (plant cane, first ratoon, and second ratoon), was 30.1% higher ( P < 0.1) than that of 'CP 89‐2143', a high recoverable sugar commercial check for muck soils. The commercial recoverable sucrose for CP 09‐1952 was not significantly higher than the check, but high cane yield resulted in 30.3% higher ( P < 0.1) sucrose yield than CP 89‐2143. CP 09‐1952 was released because of its high cane and sucrose yields on muck soils and its acceptable levels of resistance to orange rust, leaf scald, Sugarcane mosaic virus strain E, Sugarcane yellow leaf virus, and ratoon stunt. CP 09‐1952 is moderately susceptible to brown rust, and it has moderate to low freeze tolerance. CP 09‐1952 tested negative for the Bru1 quantitative trait loci, which is an indicator of brown rust resistance.